Alpinone: A positive regulator molecule of immune antiviral response in Atlantic salmon kidney cells. (January 2022) - Benavides, Almendra; Gutiérrez, Daniela; Epuyao, Nadia; Modak, Brenda; Imarai, Mónica; Valenzuela, Beatriz
Abstract: Alpinone is a flavonoid obtained from the resinous exudate of Heliotropium huascoense. This flavonoid shows antiviral activity against the infectious salmon anemia virus (ISAV), which causes severe disease in farmed Atlantic salmon. Here, we aim to elucidate mechanisms underlying the antiviral effects of the flavonoid. In this regard, we evaluated whether Alpinone can act upregulating the pattern-recognition receptor genes, i.e., the RIG-I-like, TLR3, and TLR9 genes, and the genes of the downstream signaling pathways. Transcriptional expression of the genes was analyzed using real-time PCR after 8, 24, and 48 h treatment of salmon kidney adherent cells with 15 μg/mL of Alpinone. First, we showed that Alpinone induced IFNa expression in the kidney adherent cells, indicating that this type of salmon cells is in part responsible for the effects previously reported in vivo . Upregulation of the IFN-induced myxovirus resistance (Mx) gene was also observed in the head kidney cells in response to the treatment. Overexpression reached a maximum level at 24 h post-treatment. Interestingly, Alpinone also induced upregulation of the cytosolic receptors of ssRNA, named Retinoic acid-inducible gene I (RIG-I) and Melanoma Differentiation-Associated protein 5 (MDA5), but there were no effects on the transcriptional expression of the TLR3 and TLR9 endosomal receptors. In addition, Alpinone upregulated the expression of genes encoding the main components of the RIG-I/MDA5 signaling pathways, such as the mitochondrial antiviral-signaling protein (MAVS), TNF Receptor Associated Factor 3 (TRAF3), TANK-binding kinase 1 (TBK1), I-kappaB kinase ε (IKKε), the transcription factors IRF-3, and IRF7. The increased expression of all these genes is consistent with the upregulation of IFNa and Mx mRNAs. Because BX795 completely prevents Alpinone-dependent upregulation of IFNa and IRF3, the flavonoid targets seem to be upstream of the kinases TBK1 and IKKε. Altogether, this study contributes to elucidating the mechanisms involved in Alpinone antiviral activity in fish. Alpinone can be used to counteract virus mechanisms of evasion where the onset of interferon-mediated response is prevented or delayed. Highlights: Mechanisms underlying the antiviral effects of Alpinone, a flavonoid obtained from H. huascoense, are reported. Alpinone increased the transcriptional expression of IFNa and Mx in salmon kidney cells. Alpinone upregulated the RIG-I and MDA5 cytosolic receptors and genes of the downstream pathway in salmon cells. Mechanisms of transcriptional activation of IFNa require the kinase activity of TBK1 and IKKε.